A PICOSECOND PHOTOLUMINESCENCE STUDY OF EXCITON DYNAMICS IN CD1-XMNXTE - Wong, K; Hayes, W; Ryan, J (1989)
Picosecond time-resolved photoluminescence studies have been made at temperatures down to 1.8 K and in magnetic field up to 8T of the dilute magnetic semiconductor Cd1-xMnxTe for x=0.09m 0.2 and 0.3. The dynamics of the lattice-disorder-induced and magnetically induced localisation of excitons are investigated, and it is concluded that magnetic localisation plays a major role. The luminescence for x=0.45 is discussed.